Assessment Of the Effectiveness of Complex Treatment of Chronic Generalized Periodontitis Associated Chronic Obstructive Pulmonary Disease (Eurasian Medical Research Periodical, 2024)
This article has proven the clinical effectiveness of complex pathogenetic treatment of chronic generalized periodontitis associated with chronic obstructive pulmonary disease. Clinical improvement in the condition of periodontal tissues in COPD after a course of ozone therapy is mediated by both the positive dynamics of the course of the background disease and the direct immunomodulatory, antihypoxic and antibacterial effects of medical ozone on periodontal tissues.